Clinicoradiologic and sonographic patterns of metastasis in hepatocellular carcinoma (2006)
Hepatocellular carcinoma(HCC) is usually diagnosed at an advanced stage, when little remedy could be offered. There is a need for relatively affordable, available and non- invasive tests for diagonsis, staging and detection of metastasis among individuals at risk. A clinical, chest radiographic (CXR) and abdominal ultrasonographic examination was carried out to detect and evaluate the pattern of metastasis among 53 untreated patients. One patients had clinical paraparesis with no outward evidence of metastasis. CXR revealed lund metastasis in 11(20.8%), with multifocal deposit in one. Two (3.8%) patients had perihilar lymphadenopathy and consolidation, respectively, while 18 (34%) patients had elevated right hemidiaphragm and four (7.5%) had pleural effusion. One right hemidiaphragm and four (7.5%) had pleural effusion. One had right basal pneumonitis, multiple cavitatory lesions in the lungs fields and soft-tissue wasting. No abnormality was seen in 17 (32.1%) cases. Abdominal ultrasonograph showed probe tenderness in 22(41.5%), hepatomegaly in 49(92.5%), with 33(62.3%) of these having nodularities of varying sizes. The spleen was enlarged in 10(18.9%) cases, with para-aortic lymphadenopathy. Portal hepatic lymphadenopathy was demostrated in two (3.8%) cases, while pleural effusion was detected in seven (13.2%). Metastasis is common in HCC at presentation, the lung is the commonest site of spread. Clinically visible metastasis appears uncommon in HCC.